The social construction of risk: evidence from UK banks / Dominic Roberts and Ekililu Salifu - Roberts, Dominic; Salifu, Ekililu (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This research presents empirical evidence of the perceptions of risk in UK operating banks and how these perceptions influence risk processes at these institutions. We used social constructivism to understand the views of UK managers in the banking industry. The study found that there was a divide in risk perception among risk managers in UK operating banks. Such a divide is crucial in explaining the differences in risk approach and risk processes in the banking industry. The discussion presented is based on the results of 25 semi-structured interviews. Two distinct characterizations of risk emerged from the data. One perceived risk as a calculable, measurable construct that can be managed, controlled and verified. The other conceived risk as a mixture of mathematical numerics and social ideals that engages an understanding of and appreciation for the concept. Each viewpoint represents an opportunity to fathom risk in its own context, contributing to the critical debate on risk management. The extent to which social factors influence risk decisions varied among banking institutions.